Marine Compounds Selectively Induce Apoptosis in Female Reproductive Cancer Cells but Not in Primary-Derived Human Reproductive Granulosa Cells - Fiona Young; Kirsten Benkendorff; Vicki Edwards (Marine Drugs, 2012)
Anticancer properties of tyrindoleninone and 6-bromoisatin from Dicathais orbita were tested against physiologically normal primary human granulosa cells (HGC) and reproductive cancer cell lines. Tyrindoleninone reduced cancer cell viability with IC50 values of 39 µM (KGN; a tumour-derived granulosa cell line), 39 μM (JAr), and 156 μM (OVCAR-3), compared to 3516 μM in HGC. Apoptosis in HGC’s occurred after 4 h at 391 µM tyrindoleninone compared to 20 µM in KGN cells. Differences in apoptosis between HGC and KGN cells were confirmed by TUNEL, with 66 and 31% apoptotic nuclei at 4 h in KGN and HGC, respectively. These marine compounds therefore have potential for development as treatments for female reproductive cancers.